2017
DOI: 10.1002/biot.201700113
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Bio‐Industrial Application of an Extremely Alkaline Mannanase FromBacillus subtilissubsp.inaquosorumCSB31

Abstract: Mannan-degrading enzymes have been growing interest in bio-industrial applications, such as the pulp and paper, food, and pharmaceutical industries. In this study, an extremely alkaline mannanase (MnB31) is produced by Bacillus subtilis subsp. inaquosorum CSB31. MnB31 is purified to 17.92-fold with a 21.51% yield and specific activity of 1,796.13 U mg by anion-exchange and gel filtration column chromatography. The biochemical characterization of MnB31 is performed, and the results are as follows: molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
(84 reference statements)
1
21
1
Order By: Relevance
“…CS428 (pH 12.5) [ 22 ], B. subtilis subsp. inaquosorum CSB31 (pH 12.5) [ 53 ], B. halodurans PPKS-2 (pH 11.0) [ 49 ], Bacillus sp. JAMB-750 (pH 10.0) [ 50 ] and B. cereus N1 (pH 10.0) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CS428 (pH 12.5) [ 22 ], B. subtilis subsp. inaquosorum CSB31 (pH 12.5) [ 53 ], B. halodurans PPKS-2 (pH 11.0) [ 49 ], Bacillus sp. JAMB-750 (pH 10.0) [ 50 ] and B. cereus N1 (pH 10.0) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…An extremely alkaline mannanase (MnB31) from B. subtilis subsp. inaquosorum CSB31 was found to have the highest optimal pH of 12.5 and to be stable at pH range from 5.8 to 12.5, which was the most alkaline β-mannanase reported to date [ 53 ]. In addition, almost all the reported Bacillus β-mannanases displayed optimal pH at the range from 6.0 to 12.5 (Table 2 ), which indicated that Bacillus strains were the main sources of neutral and alkaline β-mannanases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…inaquosorum CSB31," [6] the authors screen for a mannanase producer. An extreme alkaline mannanase (MnB31) enzyme was then purified and the biochemical and thermodynamic properties were examined for utilization in various biotechnological processes using different substrates.…”
mentioning
confidence: 99%